PENGAWASAN LIMBAH CAIR INDUSTRI OLEH DINAS LINGKUNGAN HIDUP( STUDI KASUS PADA PT.TAMORA AGRO LESTARI DI DESA SEROSAH KABUPATEN KUANTAN SINGINGI) - Wiwin Apia Ningsih; Abdul Sadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Kuantan Singingi Regency is one of the regencies in Riau Province which has been developing rapidly in recent years, one of which is in the oil palm plantation sector. However, due to the rapid establishment of oil palm companies, there are many industrial wastewater discharges caused by the disposal of these companies. The purpose of this study was to determine the supervision of industrial wastewater from the Environmental Agency of Kuantan Singingi Regency in the supervision of industrial wastewater and to determine the inhibiting factors for supervision of the Environmental Service Office of Kuantan Singingi Regency. Supervision activities that have been carried out are industrial liquid waste monitoring activities. The pollution found was obtained from industrial wastewater with a percentage exceeding the quality standard, the activities carried out by the Environmental Service had not been maximized so that violations of passing quality standards, and lack of firmness in imposing sanctions on companies were found phenomena. This type of research is qualitative research with a descriptive case study approach. The collection of data obtained both primary data and secondary data were collected through interviews, observation and documentation then analyzed so that conclusions can be drawn from existing research problems. The results of this study found that the supervision of the Environmental Agency in monitoring liquid waste has not been carried out optimally, this is due to several inhibiting factors, namely the ability of human resources, funds and infrastructure and company behavior. Keywords: Supervision, industrial liquid waste, quality standards